STUDI PEMANFAATAN MATA AIR UNTUK SUMBER AIR BERSIH PEDESAAN - Nasyiin Faqih (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2022)
Patakbanteng and Jojogan villages are located in the mountains of the Dieng plateau, where there are many springs, but there is no agency or party to provide clean water, although now a small part of the population still uses clean water from wells. For this reason, it is necessary to plan a clean water network for residents who do not have access to clean water. This research was conducted by collecting data in the field, including primary data covering conditions and water resources, spring discharge, elevation and pipelines to consumers, while secondary data covering population, population growth ratio and village maps. The spring discharge of Sendang Panguripan Gunung Prau is 172 m3/sec, to meet the water needs of the people of Patakbanteng Village and Jojogan Village with a population ratio in the 15th plan year is 4193 people according to the pre-design calculation of the required discharge of 5.27 lt/sec.